Coulomb and tunneling-coupled trilayer systems at zero magnetic field - Miravet Martinez, Daniel (2016)
The ground-state electronic configuration of three coupled bidimensional electron gases has been determined using a variational Hartree-Fock approach, at zero magnetic field. The layers are Coulomb coupled, and tunneling is present between neighboring layers. In the limit of small separation between layers, the tunneling becomes the dominant energy contribution, while for large distance between layers the physics is driven by the Hartree electrostatic energy. Transition from tunneling to Hartree dominated physics is shifted towards larger layer separation values as the total bidimensional density of the trilayers decreases. The interlayer exchange stabilizes a "balanced" configuration, where the three layers are approximately equally occupied; most of the experiments are performed in the vicinity of this balanced configuration. Several ground-state configurations are a consequence of a delicate interplay between tunneling and intersubband exchange.